Organizational health literacy in German hospitals: a cross-sectional survey among hospital managers - Nicola Häberle; Jonas Lander; Marie-Luise Dierks; Eva Maria Bitzer (BMC, 2024)
Abstract Background Organizational health literacy (OHL) describes conditions and measures in healthcare institutions to enable patients to make good health-related decisions. By providing easy access to and appropriate communication of understandable information to use and navigate the facility, healthcare organizations can contribute to strengthening patients' health literacy and self-management. The extent of OHL implementation in German hospitals remains largely unknown. This study aims to fill this gap in our knowledge by investigating OHL-related activities reported by hospital managers. Methods Between November and December 2022, we conducted a national online survey among medical, nursing and administrative hospital managers with hospitals that operate more than 50 beds. The data were collected via the health literate health care organization ten item questionnaire (HLHO-10) and supplemented by sociodemographic questions and an open-ended question. We applied variance and correlation analyses to investigate the data. Results Of 3,301 invited hospital managers, 371 participated in the survey (response rate 11%). The overall mean score for HLHO-10 was 4.6 (SD = 1.1) on a 7-point Likert scale, indicating a moderate level of OHL implementation. Hospital managers stated that hospitals concentrate on helping patients find their way around and communicating the costs of treatment transparently and clearly; conversely, that active patient participation in the design and evaluation of health information is rare in care settings, and that health information is seldom provided to patients through a range of media. For the practical implementation of the OHL, most hospital managers mentioned activities regarding communication standards, such as providing information materials. Conclusions Given their unique position as hubs of human interaction, hospitals provide an ideal opportunity to promote the adoption of OHL. By actively involving patients, hospitals can better tailor their approaches to meet patient needs and preferences. Compared to studies from oncology centres in Germany and 20 Italian hospitals, the average HLHO-10 score of this study is lower. While some aspects of OHL are already embedded in inpatient care, it is imperative that OHL is thoroughly embedded in the hospitals' organizational culture and plays a fundamental role in the daily operations of the institution. This could be done, for instance, by more explicitly addressing the topic of health literacy in staff communication training.